PENGARUH GAYA KEPEMIMPINAN KARISMATIK TERHADAP SEMANGAT KERJA PEGAWAI DI KANTOR DESA HILIABOLATA - Isman Julfianus Telaumbanua (Pareto: Jurnal Riset Bisnis dan Manajemen, 2022)
The study aims to determine the effect of charismatic leadership style on employee morale at the Hiliabolata village office. This type of research is a quantitative research that is causal to see the relationship of variables to the object under study. The population and sample in this study amounted to 31 employees. The analytical method used in this research is simple linear regression analysis. The results of this study indicate that there is a significant influence between charismatic leadership style on employee morale at the Hiliabolata village office. In this study, a simple linear regression equation was obtained, namely: Y=10.202 + 0.713X, the T count value was 8.111 > T table 1.549, and a significant level of 0.000 < 0.05, then the decision was Ha accepted and Ho was rejected, meaning that the charismatic leadership style variable had a positive effect and significant to employee morale. Then simultaneously there is a positive influence between the independent variable charismatic leadership style (X) on the dependent variable employee morale (Y) using the SPSS 21.0 for the windows evaluation version program, the R Square value is 0.649 or 69.4%. The results of hypothesis testing (t-test) T-count value obtained a value of 8.111 > T-table value of 1.549 with 29 degrees of freedom (31-2) at the = 0.05 because 0.000 < 0.05 it can be concluded that charismatic leadership style effects work morale employee at the Hiliabolata village office.